The Coronavirus Disease 2019 (COVID-19), Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2), Omicron (B.1.1.529) Variant of Concern and the New Omicron Subvariant BA.2: What We Know So Far? - Rahman, Mohammad Atiqur (Jalalabad Medical Journal, 2025)
Abstract not available Jalalabad Med J 2022; 19 (2): 43-46